Expression of starch-binding factor CBM20 in barley plastids controls the number of starch granules and the level of CO2 fixation. (8th September 2019) - Zhong, Yingxin; Sagnelli, Domenico; Topbjerg, Henrik Bak; Hasler-Sheetal, Harald; Andrzejczak, Olga Agata; Hooshmand, Kourosh; Gislum, René; Jiang, Dong; Møller, Ian Max; Blennow, Andreas; Hebelstrup, Kim Henrik
Abstract : Interference in protein–starch interactions in barley by the expression of an exogenous high-affinity starch-binding factor (Carbohydrate-Binding Motif 20, CBM20) reveals a link between starch granule biosynthesis and the level of photosynthesis. Abstract: The biosynthesis of starch granules in plant plastids is coordinated by the orchestrated action of transferases, hydrolases, and dikinases. These enzymes either contain starch-binding domain(s) themselves, or are dependent on direct interactions with co-factors containing starch-binding domains. As a means to competitively interfere with existing starch–protein interactions, we expressed the protein module Carbohydrate-Binding Motif 20 (CBM20), which has a very high affinity for starch, ectopically in barley plastids. This interference resulted in an increase in the number of starch granules in chloroplasts and in formation of compound starch granules in grain amyloplasts, which is unusual for barley. More importantly, we observed a photosystem-independent inhibition of CO2 fixation, with a subsequent reduced growth rate and lower accumulation of carbohydrates with effects throughout the metabolome, including lower accumulation of transient leaf starch. Our results demonstrate the importance of endogenous starch–protein interactions for controlling starch granule morphology and number, and plant growth, as substantiated by a metabolic link between starch–protein interactions and control of CO2 fixation in chloroplasts.